2019
DOI: 10.1136/bmjopen-2018-028224
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic knowledge, attitudes and practices: new insights from cross-sectional rural health behaviour surveys in low-income and middle-income South-East Asia

Abstract: IntroductionLow-income and middle-income countries (LMICs) are crucial in the global response to antimicrobial resistance (AMR), but diverse health systems, healthcare practices and cultural conceptions of medicine can complicate global education and awareness-raising campaigns. Social research can help understand LMIC contexts but remains under-represented in AMR research.ObjectiveTo (1) Describe antibiotic-related knowledge, attitudes and practices of the general population in two LMICs. (2) Assess the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
7
55
0
Order By: Relevance
“…Yet mainstream public health education messages are not appropriate for those experiencing hardship and abject poverty on a daily basis [ 11 ]. Educational campaigns need to be complemented by upstream drivers of AMR such as poverty and unemployment and structural violence [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet mainstream public health education messages are not appropriate for those experiencing hardship and abject poverty on a daily basis [ 11 ]. Educational campaigns need to be complemented by upstream drivers of AMR such as poverty and unemployment and structural violence [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies on AMR showed that addressing the social determinants of poverty is an essential yet neglected step in addressing AMR [ 12 ]. In LMICs structural, social, political and economic barriers impede access to prescription medicines, and health system development challenges compromise intervention efforts [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The international AMR community now acknowledges that, for maximal effect, large-scale awareness campaigns should be integrated within industry-wide AMR behavioural policy strategies [4,17]. Our preliminary data suggest that, by rapidly and effectively engaging rural aquaculture communities, digital communications could effectively support this.…”
Section: Discussionmentioning
confidence: 85%
“…(25) Previous study has demonstrated that the link between antibiotic knowledge and attitude towards antibiotic is weak in the context of LMIC. (26) As people from rural areas become more nancially secure, they also become more empowered and assertive towards their health.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, their attitude towards handling antibiotic is inappropriate not because of ignorance but because they are now able to exercise this assertiveness. (26) Factors associated with inappropriate attitude towards antibiotic usage…”
Section: Discussionmentioning
confidence: 99%